Concepciones y prácticas de la evaluación del aprendizaje en la carrera de pedagogía de laUPS sede Quito, desde la percepción de los docentes - Roya, Anne Falatoonzadeh (2016)
This investigation studies the perception of learning evaluation of Polytechnic Salesian University, Faculty of Education, Campus Quito. The main objective is to identify the authenticity of learning evaluation of this faculty of the university. The object of study is authentic learning evaluation, which is an alternative method in the face of the limitations and difficulties of more traditional evaluations. The quantitative method of investigation collected information from the professors of the faculty. The investigation performed between March and September 2015 provided information from the professors, which was analyzed according to three criteria: realism, professional identity and significance. The results of the investigation indicate a perception of authenticity in the learning evaluation process from the perspective of the professors of the faculty, which implies that the assignments are realistic, a reflection of the teaching community and are relevant.